Modelo Matemático No-Lineal para un Servosistema Neumático de Posicionamiento Preciso - Germán A. Bacca; Víctor J. De Negri; Yesid Assaf (TecnoLógicas, 2010)
In this paper, a nonlinear mathematical model of a servo pneumatic positioning system is developed in detail. The systemis compound in its basic structure for a double-acting cylinder without piston rod which is controlled by a proportional valve.For the elaboration of model were taken in account the cylinder dynamics, work fluid properties and valve characteristics. Themass flow model is based on the model of standard ISO 6358, and the system parameters were estimated by means of nonlinear optimization techniques from experimental data in transient state. Validation of system dynamic model was made for different input signals and compared with experimental results.